2018
DOI: 10.1136/bmjopen-2017-015928
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of rehabilitation intervention outcomes of adult and paediatric patients with infectious encephalitis

Abstract: ObjectiveAlthough a range of rehabilitation interventions have been applied to restore function after infectious encephalitis, there is a lack of literature summarising the benefits of these interventions. This systematic review aims to synthesise current scientific knowledge on outcome measures following rehabilitative interventions among children and adults with infectious encephalitis, with a specific focus on the influence of the age, sex, baseline status and intervention type.Search strategyFive scholarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 75 publications
0
15
0
1
Order By: Relevance
“…In our case, patient's behavior status, anxiety and cephalalgy are mandatory to be monitor in the future visits. The quality of the rehabilitation care is not dependent of age, sex, type of infectious agent or intervention type, but is related more to establishing the correct diagnosis, the initial clinical picture, as well as the unique central nervous system characteristics of each individual (6). The particularities of this case lay in the atypical symptomatology of encephalitis manifested through headache, without the alteration of the conscious state or other neurological signs, vegetative epileptic crisis manifested through high blood pressure, associated with cortical laminar necrosis and in the fact that the pathogen agent wasn't detected through the currently available methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, patient's behavior status, anxiety and cephalalgy are mandatory to be monitor in the future visits. The quality of the rehabilitation care is not dependent of age, sex, type of infectious agent or intervention type, but is related more to establishing the correct diagnosis, the initial clinical picture, as well as the unique central nervous system characteristics of each individual (6). The particularities of this case lay in the atypical symptomatology of encephalitis manifested through headache, without the alteration of the conscious state or other neurological signs, vegetative epileptic crisis manifested through high blood pressure, associated with cortical laminar necrosis and in the fact that the pathogen agent wasn't detected through the currently available methods.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the chronic deficits that the patient may experience include neurological impairments, movement disorders, aphasia, behavioral abnormalities, and intellectual deficit. The general outcome can be improved by rehabilitation methods which can be applied according to each case particularity (6). Cognitive therapy interventions, measuring for example memory and language processing, have a positive change in neuropsychological tests from baseline to follow-up, but with no complete recovery for the majority of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Для смягчения последствий инфекционного энцефалита применялись различные вмешательства, в том числе с использованием когнитивной терапии (9 исследований), поведенческой терапии (5 исследований), физиотерапии (2 исследования) или 2 или более методов лечения (4 исследования). Из-за их клинической и методологической неоднородности метаанализ не проводился [11].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…Rehabilitative treatment modalities should be considered in this population, as there is the potential for at least partial recovery [3]. A prospective evaluation of cognitive recovery across encephalitis subtypes showed that the majority improved over time [4].…”
mentioning
confidence: 99%